2018
DOI: 10.1089/mdr.2017.0152
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Class 1 Integrons, and Disruption of carO and dacD by Insertion Sequences Among Acinetobacter baumannii Isolates in Tehran, Iran

Abstract: Acinetobacter baumannii is an important nosocomial pathogen which causes a wide range of infections. In this study, we addressed the role of class 1 integron, ISAba1 and ISAba125 associated with antimicrobial resistance in 72 clinical isolates of A. baumannii collected from clinical settings in Tehran, Iran. Moreover, to study the clonal relatedness of strains, repetitive extragenic palindromic-PCR (rep-PCR) assay was carried out. PCR revealed that bla-like, bla-like, bla-like, bla-like, bla, integrase gene (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…[ 10 , 25 ] IS Aba1 has been shown to be associated with bla OXA-23 -like- and bla OXA-51 -like-related CR of A. baumannii . [ 26 , 27 ] Its absence in the upstream of OXA-51-like but presence in that of OXA-23-like revealed that OXA-51-like was not as important as OXA-23-like in contributing to the CR phenotype in our study. This was proofed by the null expression of OXA-66/-69 in the strains.…”
Section: Discussionmentioning
confidence: 50%
“…[ 10 , 25 ] IS Aba1 has been shown to be associated with bla OXA-23 -like- and bla OXA-51 -like-related CR of A. baumannii . [ 26 , 27 ] Its absence in the upstream of OXA-51-like but presence in that of OXA-23-like revealed that OXA-51-like was not as important as OXA-23-like in contributing to the CR phenotype in our study. This was proofed by the null expression of OXA-66/-69 in the strains.…”
Section: Discussionmentioning
confidence: 50%
“…A BLAST search with the first 300 nt of the aadB transcript yields hits to Ͼ100 A. baumannii genomes, with coverage ranging from 73% to 100%. Integrons encoding aminoglycoside modifying enzymes, including aadB, are also widely reported in the A. baumannii literature (45)(46)(47)(48)(49)(50). As the ϳ300-nt sRNA appears to be encoded mostly within the integron promoter region, it is possible that other integrons, even those not harboring aadB, still contain this transcript.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Egypt revealed that ISAba1 has been inserted in carO gene leading to interruption of its expression [173]. A report about an insertion sequence disrupting the gene encoding the penicillin binding protein PBP6b (also known as dacD) was identified in an endemic carbapenem-resistant clone in a Spanish hospital [174]. Additionally, a collective set of changes involving disruptions in carO and dacD, as well as carbapenemase production, developed resistance to carbapenems among clinical isolates of A. baumannii [175].…”
Section: Nonenzymatic β-Lactam Resistance Mechanismsmentioning
confidence: 99%